The Meaning of the Emblem of the Bandung Raya Regional Government - Noviantono, Nurcahyo Eko; Maulina, Rini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The Bandung Raya area is contained in the Bandung basin, including the City of Bandung, Bandung Regency, West Bandung Regency, and Cimahi City. Based on government regulations, every regional government has emblems that function as an identity and binder of the socio-cultural unity of regional communities. This study aims to reveal the meaning contained in the emblem of local government. The research location was conducted in the city of Bandung, West Java. Previous research that has been carried out has not studied the meaning of regional emblems based on visual elements.  The research conducted used qualitative methods to reveal the visual meaning contained in the emblem of the Bandung Raya area. This study aims to gain knowledge about the meaning of local government emblems and helps add science to the field of visual communication design. The research found that the elements contained in the emblem of Bandung Raya are related to the vision and mission of the city and regency. The regional logo design depicts the region's potential, it was found that the symbols contained in the regional coat of arms have the meaning and expectations of the local government for its people.